Self-Efficacy and Academic Procrastination among Muhammadiyah Sidoarjo Students: Efikasi Diri dan Penundaan Akademik di Kalangan Mahasiswa Muhammadiyah Sidoarjo - Habibah, Inayatul; Dewanti, Ririn (Indonesian Journal of Education Methods Development, 2025)
General Background: Academic procrastination is a common problem faced by university students and often leads to decreased academic performance. Specific Background: One psychological factor associated with procrastination is self-efficacy, which reflects an individual’s belief in their ability to complete academic tasks. Knowledge Gap: Although previous studies have examined this relationship, limited research has focused on advanced-level students in Indonesian higher education. Aims: This study aimed to examine the relationship between self-efficacy and academic procrastination among students in semesters 10, 12, and 14 at Muhammadiyah University of Sidoarjo. Results: Using a correlational quantitative approach with 292 participants selected through non-probability sampling, data were collected using validated scales of self-efficacy and academic procrastination (reliability 0.825 and 0.902). Spearman’s rho analysis revealed a significant negative correlation, indicating that higher self-efficacy was associated with lower academic procrastination. Self-efficacy contributed 17.6% to the variance in academic procrastination. Novelty: This study provides empirical evidence of the psychological dynamics influencing procrastination in late-semester students, a population often overlooked in similar research. Implications: Findings highlight the need for interventions that strengthen students’ self-efficacy to reduce procrastination and improve academic performance. Highlights: Self-efficacy shows a negative correlation with academic procrastination. Self-efficacy explains 17.6% of procrastination variance. Focuses on advanced-level Indonesian university students. Keywords: Self-Efficacy, Academic Procrastination, Higher Education, Psychology, Students